Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia) - Heinicke, Matthew P.; Turk, Dilara; Bauer, Aaron M. (Zootaxa, 2017)
The gekkonid genus Goggia includes eight described species of mostly small-bodied rock dwelling gecko endemic to the southwestern portion of southern Africa, in South Africa and extreme southern Namibia. Previous studies focused on Goggia have employed external morphology and allozyme electrophoresis, but no sequence-based molecular phylogeny of the group has been produced. We have generated a molecular phylogeny of Goggia including all named species and multiple individuals within each species, using sequences of the mitochondrial gene ND2 and nuclear genes RAG1 and PDC. The phylogeny depicts a basal divergence between eastern and western species of small-bodied Goggia, with additional divergences also showing structure strongly correlated with geography. Goggia lineata and G. rupicola are shown to be non-monophyletic, and examination of external morphology supports the distinctiveness of these lineages. We describe two new species to accommodate the southern lineages of “G. lineata” and “G. rupicola”: Goggia incognita sp. nov. and Goggia matzikamaensis sp. nov. Both new species are separated from their northern relatives by geographic barriers: the Knersvlakte plain for G. incognita sp. nov. and G. lineata, and the high Kamiesberg mountains for G. matzikamaensis sp. nov. and G. rupicola. The possible roles of geography, ecology, and climate in promoting diversification within Goggia are discussed.